Consumer ethics among young consumers in developing countries: A cross national study - Denni Arli (2018)
Purpose - The present study aims to examine the similarities and differences between young consumers in Indonesia and Thailand based on actionable and strategy-yielding marketing variables (e.g. Machiavellianism, ethical orientations, trust, opportunism and materialism) and, second, it examined the impact of these variables on consumer ethics. Design/methodology/approach - A convenience sample of university students from a large private university in Yogyakarta (Indonesia) and a large public university in Chiang Mai (Thailand) were asked to complete a survey that incorporated scales to measure consumers' ethical beliefs, specifically, Machiavellianism, ethical orientation, opportunism, trust and materialism, as well as demographic classification questions. Findings - The findings showed that young Indonesian and Thai consumers display similarities on most of the constructs. Moreover, the study found that personal moral philosophies (i.e. idealism and relativism) and trust strongly influence their judgment in ethically intense situations in both countries. Research limitations/implications - The current study has several limitations, especially the use of convenience sampling that may limit the generalizability of the findings. Students in Indonesia and Thailand may behave differently from general consumers or other cohorts with regards to their ethical judgments. Practical implications - Because personal ethical positions are developed over a lifetime of experiences in dealing with and resolving moral issues, schools and universities should intervene and educate youth on acting in ways that are consistent with moral rules. Currently, universities and schools in Indonesia and Thailand and many other countries in developing countries do not promote this knowledge to students. Originality/value - This is one of the first studies exploring consumer ethics in Indonesia and Thailand.